Potential Preventive Strategies for Amyotrophic Lateral Sclerosis - Kuraszkiewicz, B.; Goszczyńska, H.; Podsiadły-Marczykowska, T.; Piotrkiewicz, M.; Andersen, P.; Gromicho, M.; Grosskreutz, J.; Kuźma-Kozakiewicz, M.; Petri, S.; Stubbendorf, B.; Szacka, K.; Uysal, H.; et al. (Frontiers in Neuroscience, 2020)
It may seem useless to propose preventive measures for a disease without established pathogenesis and successful therapy, such as Amyotrophic Lateral Sclerosis (ALS). However, we will show that ALS shares essential molecular mechanisms with aging and that established anti-aging strategies, such as healthy diet or individually adjusted exercise, may be successfully applied to ameliorate the condition of ALS patients. These strategies might be applied for prevention if persons at ALS risk could be identified early enough. Recent research advances indicate that this may happen soon.